Cardiometabolic multimorbidity and frailty in middle-aged and older adults: a cross-nationally harmonized study - Zhou, Kunyan; Wang, Ao; Yi, Ke (Frontiers in Public Health, 2025)
BackgroundCardiometabolic diseases are prevalent among ageing populations and have a close association with frailty. However, the cumulative impact multiple cardiometabolic diseases have on frailty remains underexplored.MethodsThis study used data from four international cohorts – HRS, CHARLS, ELSA and SHARE – to examine the correlation between frailty and cardiometabolic diseases (CMD). The frailty index was used for assessing frailty and statistical analyses were performed as a means of analysing the correlation between the number of cardiometabolic conditions and frailty severity. Linear regression models were employed to evaluate the associations between CMD and frailty severity.ResultsThe study found that as the number of cardiometabolic diseases increased, the frailty index rose significantly [one disease, β = 7.80 (95% CI: 7.70 to 7.90) p < 0.05; two diseases, β = 17.92 (95% CI: 17.76 to 18.08) p < 0.05; three diseases, β = 28.79 (95% CI: 28.41 to 29.17) p < 0.05]. Stroke was found to have the most pronounced impact on frailty (β = 12.34 [95%CI 12.20 to 12.48] p < 0.05) and the coexistence of multiple conditions served to amplify the symptoms of frailty.ConclusionThis study highlights the compounded impact multiple cardiometabolic diseases have on frailty and also emphasizes the necessity for early intervention.